2003
DOI: 10.1016/s1010-7940(02)00677-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high intensity transient signals on the choice of mechanical aortic valve substitutes

Abstract: We conclude that bileaflet mechanical valve prostheses produce HITS even in their optimum orientation. HITS following bileaflet valve replacement have an unstable nature and might be composed of nitrogen and platelets. Tilting disc valves in their optimum orientation provide almost physiological conditions with HITS measured in the same range as bioprosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
3
19
0
1
Order By: Relevance
“…It is obvious that the large opening of the asymmetrically constructed valves must be positioned to pass the larger part of the systolic stroke volume. This was confirmed in the above mentioned studies [2,7,[15][16][17][18], which showed that the flow downstream the monoleaflet valves is very sensitive to rotation with the best profiles achieved when the large orifice faces the noncoronary sinus.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…It is obvious that the large opening of the asymmetrically constructed valves must be positioned to pass the larger part of the systolic stroke volume. This was confirmed in the above mentioned studies [2,7,[15][16][17][18], which showed that the flow downstream the monoleaflet valves is very sensitive to rotation with the best profiles achieved when the large orifice faces the noncoronary sinus.…”
Section: Discussionsupporting
confidence: 63%
“…By further subdividing mechanical valves into monoleaflet and bileaflet valves, we found that receiving a monoleaflet aortic valve is an independent risk factor for low flow in vein grafts. Nevertheless, six studies found that monoleaflet mechanical valves in their optimal orientation demonstrate a superior hemodynamic performance [2,7,[15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Laas et al 19 also studied the high-intensity transient signal caused by free emboli after St. Jude Medical MHV implantation and demonstrated that the combination of valve tilt and insertion of subannular pledgets led to a significant increase in the thromboembolic potential of the valve, likely caused in part by increased platelet activation.…”
Section: Mechanical Heart Valves (Mhvs) and Thromboembolismmentioning
confidence: 99%
“…29 In 30 patients with bileaflet valves, a reduction of MESs by 16% to 41% after administration of acetylsalicylic acid of 81 to 531 MESs/h was demonstrated. 25 Additionally, a higher number of MESs was found in patients with valve obstruction. 30 Successful thrombolysis led to a marked decrease of MESs, whereas the number of MESs remained almost stable after unsuccessful thrombolysis.…”
Section: Mess In Prosthetic Heart Valvesmentioning
confidence: 99%
“…23 This is why inhalation of concentrated oxygen has been used to suppress cavitation formation to distinguish solid thromboembolic from gaseous material. 14,24,25 Because the solubility of oxygen in blood is Ϸ5 times greater than that of nitrogen, the blood is preferably saturated with oxygen instead of nitrogen. Oxygen cavitation is short-lived, which means that many oxygen bubbles do not reach the brain at all.…”
Section: Mess In Prosthetic Heart Valvesmentioning
confidence: 99%